MODELLING OF POLICY ANALYSIS OF INDONESIAN FOOD PROCESSED INDUSTRY USING SYSTEM DYNAMICS APPROACH - MARITO (NIM 23406054), RIRIS
Industrial development of fruit processed industry in the future must orient at improvement of production volume, because level of consumption per kapita juice in Indonesia always experiences improvement. This thing results juice import volume stepping into Indonesia also experiences increase because available domestic juice product cannot fulfill market demand. The objective of this study was to formulate policies that can be used in national fruit processed industry, so that the performance of this industry can be improved. Fruit processed industry model that was developed here, was based on condition of juice industry now and Forrester's Nasional industry model. This model consists of seven sub systems that are related to each other, that is production and capital sub system, domestic demand, export demand sub system, raw material sub system, manpower sub system, population sub system, and also financial and government sub system. Policy scenarios wich are implemented to built model are raw material policy scenario, manpower policy scenario, domestic market policy scenario, export policy scenario, investment policy scenario, and the combintion of those policies. While performance measure which wish to be reached in this research are to grow up production rate, demand rete, absorbtion of labour, and invesment growth. Juice production rate gives best result after applied by raw material policy scenario, that is increasing production growth reachs 11,05%. Domestic demand rate of juice gives best result after applied by domestic market policy scenarios, that is increasing domestic demand growth reaches 5,10%. Juice export demand rate gives best result after applied by export market policy scenario, that is increasing demand growth of export reachs 17,67%. Level of absorption of manpower at juice industry gives best result after applied by domestic market policy scenarios, that is increasing absorption growth of manpower reaches 7,98%. Level of growth of industrial investment of juice gives best result after applied by investment promotion scenario, that is increasing growth of investment reaches 3,07%. Simulation result done indicates that fourth of policy scenarios area applied able to give repair influence significant to behavior of system performance either in short term and also on a long term. In general policy from bid side gives behavior of industry performance that is better than policy from demand side. During the time, government is more relying only policy from side demand for develops industry. Though policy from demand side can influence demand increase of market, if is not made balance to ably industry in doing activity of its production, hence industrial performance on a long term will experience degradation.